Avaliação do Nível de Proficiência Digital dos Professores dos Institutos Federais do Estado do Maranhão - Lima, Jorcelyo Alencar (Universidade Federal do Tocantins, 2021)
This scientific investigation is based on the interface of knowledge of the contemporary, interconnected, competitive and globalized world, with technological resources that favor and enable all professional actions, among them the process of teaching us the learning of educational institutions, whose function fundamental is the intellectual and professional training of the subjects. In this sense, a Dissertation entitled Evaluation of the level of digital proficiency of teachers from the Institutos Federais do Maranhão, with the fundamental objective of evaluating the level of digital proficiency of teachers in the Campi of Federal Institutes in the State of Maranhão. Based on theories about teaching knowledge and practice; the dialogism between education and technology and public policies, a field research carried out at the Federal Institutes of Education of the state of Maranhão, with the exploratory and descriptive objective, within a universe of 1990 teachers, with a minimum age of 20 years and maximum 75 years old. In addition to the variables gender and age, educational level, area of activity, work regime and employment relationship with the institution were also considered. The questionnaire proposed by the DigCompEdu “CheckIn” EU Science Hub (Science Center of the European Union) was used to analyze the self-reflection of the IFMA teachers on digital competences in Education, composed of 21 questions organized according to the levels of competence, divided into 06 areas, covering questions about professional involvement; digital technologies and resources; teaching and learning; evaluation; student training; and promoting students' digital competence. In view of the data analysis, it was found that the variables age and gender are the ones that least determine variation with regard to digital competence, having the greatest area of training and educational level of teachers. Thus, since teaching not only interfaces with technology, but that it has it as an indispensable and inherent tool in its thinking and doing, it is essential that public policies on technology in education are created so that it goes beyond the acquisition of materials , favor the training of teachers for the development of digital skills for a world that has appropriated tools so essential for the development of human cognitive, intellectual and professional capacities.